Serological and biochemical study of hepatitis B patients, a report from the southeast of Iran. (February 2018) - Shahramian, Iraj; Rostami, Daryoush; Sharafi, Elham; Sargazi-aval, Omolbanin; Delaramnasab, Mojtaba; Bazi, Ali
Aim: Clinical importance of HBeAg and HBeAb positivity was assessed in 309 patients with chronic HBV infection.Patients & methods: Clinical, biochemical and serological data were extracted from medical archives over a 10-year period (2004–2014).Results: HBeAg and HBeAb were positive in 46 (14.8%) and 221 (71.5%), respectively. Persistent elevation of AST and ALT enzymes were seen in 73 (21.2%) and 98 (30.1%) of the patients, respectively. HBeAb positivity rendered a significant protective effect against the elevated enzyme levels (odds ratio = 0.03; 95% CI: 0.003–000.3; p = 0.006 for AST, and odds ratio = 0.05; 95% CI: 0.007–000.4; p = 0.007 for ALT).Conclusion: Immune reaction against HbeAg in the course of chronic HBV infection rendered a protective factor against hepatic enzymes elevation.